ADENOSMA CAERULEUM AS AN ADJUNCT IN HEPATITIS AND ELEVATED LIVER ENZYMES: A TRADITIONAL AND MODERN INTEGRATIVE REVIEW (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize traditional and modern evidence on Adenosma caeruleum (Nhan tran) for supporting the management of hepatitis and elevated liver enzymes, and to clarify its distinction from Artemisia capillaris (Yinchen).Methods: Narrative review of Vietnamese and international sources (2000-2025) from PubMed, ScienceDirect and national pharmacopeial materials. We summarized botany, phytochemistry, pharmacology, safety, and clinical relevance; and contrasted the evidence base with Yinchen.Results: A.caeruleum, a Plantaginaceae herb widely used in Vietnam, provides essential oils dominated by mono-sesquiterpenes (e.g., thymol/carvacrol chemotypes) and iridoids. Experimental studies indicate antioxidant and anti‑inflammatory activities and bile‑promoting traditional use, suggesting potential hepatoprotective support. However, human clinical trials specific to A.caeruleum for hepatitis or aminotransferase reduction are lacking; most clinical hepatology data in the “Nhan tran” vernacular actually refer to A.capillaris. Quality standards for Herba Adenosmatis caerulei exist in the Vietnamese pharmacopeia, and traditional formulas use 10-30 gram/day as decoction or tea. Safety is generally favorable when used as crude herb; caution is advised with concentrated essential oils, pregnancy, gallstone obstruction, and drug interactions.Conclusion: A.caeruleum may serve as an adjunct for symptomatic relief (cholagogic, anti‑inflammatory) in mild hepatic dysfunction, but current evidence does not support it as a primary therapy for hepatitis or for reliably lowering ALT/AST. Clear labeling to avoid confusion with A.capillaris, adherence to quality standards, and integration with guideline‑based care are recommended.
Keywords: Adenosma caeruleum, Nhan tran, hepatitis, liver enzymes, traditional medicine, adjunct therapy.